See what a seal can do - Butterworth, Christine (Candlewick Press, 2013)
A lyrical portrait of seal characteristics and life explains how seals appear to be slow and sleepy creatures on land but are powerful, graceful and dynamic animals under the water who cleverly outmaneuver predators and skillfully catch fishy dinners.